Minimisation of environmental effects related with storing fly ash from combustion of hard coal - Obraniak, Andrzej; Gluba, Tadeusz; Ławińska, Katarzyna; Derbiszewski, Bogdan (Oficyna Wydawnicza Politechniki Wrocławskiej, 2018)
The tests have been carried out on granulation of fly ash that may significantly reduce the consequences of its storage and transport harmful to the environment, mainly secondary dusting. Granulation was conducted using a disk granulator. The experiments involved the evaluation of a loose additive (bentonite) impact, the analysis of moisture content and water and sodium glass impact, the optimisation of the added bentonite amount and the granulated product breaking resistance test. The were examined such parameters as the ratio of ash to fillers, the amount of supplied binding liquid (distilled water or waterglass) and the place of its feeding. The addition of bentonite to bed (ash) made it possible to completely granulate the material. The introduction of waterglass in place of demineralised water produced the desired effect.
Environment Protection Engineering. Vol. 44, 2018, nr 4, s. 177-189
Keywords: ochrona środowiska; inżynieria środowiska; czasopisma